The practical situation and parameters of formation of professional pedagogical culture for students of physical culture education - B.B.Karimov (European International Journal of Pedagogics, 2025)
The article examines professional pedagogical culture, the main mechanisms used in the development of professional pedagogical culture, the practical situation and parameters for the formation of professional pedagogical culture of physical education students.